Planarian RNAi knockdown: feeding once might just be enough - Reho, Guillaume; Menger, Yannick; Lelièvre, Vincent; Cadiou, Hervé (Frontiers in Neuroscience, 2025)
RNA interference (RNAi) is a powerful tool to knock down the expression of genes of interests. In planarians, a popular animal model to study development and regeneration processes, RNAi is easily set up by feeding the animals double-stranded RNA (dsRNA). However, there is no consensus in the literature on the amount of dsRNA needed to efficiently knock down gene expression, nor on the lasting effect of this knockdown. Here, we exposed the worms to two RNAi protocols, either feeding them dsRNA only once or three times in the span of a week. To observe the gradual loss and retrieval of nociceptive phenotypes, we exposed the worms to Allyl Isothiocyanate (AITC), an irritant and TRPA1 receptor agonist, while we knocked down the expression of the TRPA1 receptor and performed behavioral assessments over 11 weeks. We showed that feeding planarians once was sufficient to induce similar phenotypes as feeding them three times, that also lasted as long. These insights are useful to refine RNAi protocol timelines and may save some valuable resources.